Employment Effects of Different Innovation Activities: Microeconometric Evidence - Bettina Peters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Extending a recently developed multi-product model and distinguishing between different product and process innovation activities, this paper reports new results on the relationship between innovation and employment growth in manufacturing and service firms in Germany. The model is tailor-made for analysing firm-level employment effects of innovations using specific information provided by CIS data. It establishes a theoretical link between employment growth and innovation output. The econometric analysis confirms that product innovations have a positive impact on employment. In contrast to previous studies, this effect is independent of the novelty degree. Moreover, different employment effects between manufacturing and service firms regarding process innovations were found. Finally, from a cross country perspective the results for Germany are similar to those found for Spain and the UK.
Older version: http://hdl.handle.net/10419/24079
Keywords: O32; L60; L80; O33; C21; J23; 330; Innovation; employment; applied econometrics; manufacturing; services; Innovation; Beschäftigungseffekt; Verarbeitendes Gewerbe; Dienstleistungssektor; Schätzung; Deutschland